Education as a disputed field between peasants and agribusinesses (2021)
In this article we present an enquiry on the ways in which the environmental conflictbetween the peasants and the agribusiness model in Santiago del Estero, Argentina, is expressed in the field of education. In order to carry out this qualitative study, we first conducted semistructured interviews and participant observations in meetings and workshops in peasant communities in the mountains of Guasayán. We then reviewed documents from peasant organizations in the province of Santiago del Estero. This was followed by successive cycles of open and axial analysis. The results were structured along the following conceptual axes: (1) school system in peasant territories, (2) learning by participation in communities and in the movement and (3) Agroecology School. The conclusion is that the field of education is one of the contexts of dispute between the peasants and agribusiness in the former’s struggle for its own (re)existence. We thus highlight the importance of looking not only at how environmental conflicts are represented in the educational system, but also at the practices of educational agents in such conflicts.